Penguatan Layanan Keluarga Maslahat Berbasis Maqashid Syariah dan Sosiologi Hukum di Kabupaten Bogor - Abdurrahman Hakim; Agus Putrono; Abdul Latif Anshori; Abdul Husenudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Strengthening family resilience has become a strategic agenda in social development and the implementation of family law in Indonesia. This article aims to analyze the implementation and enhancement of Maslahah Family Services based on Maqasid al-Shariah and the Sociology of Law in developing an integrative model of Indonesian family law in Bogor Regency. This Community Service (PkM) program employed a qualitative approach using a case study method. Data were collected through semi-structured interviews, participatory observation, and document analysis involving Heads of Religious Affairs Offices (KUA), Islamic religious counselors, members of the Maslahah Family Working Group, community leaders, and participating families. The findings indicate that the strengthening program significantly improved family literacy regarding maslahah values, legal awareness, and community participation in preventing family conflicts. Furthermore, the program facilitated the integration of religious, social, educational, economic, and legal services, thereby reinforcing the role of KUA as a family service center. The results demonstrate that the integration of Maqasid al-Shariah and the Sociology of Law effectively bridges the gap between legal norms and social realities through a participatory, preventive, and sustainable service model. This study contributes to the development of an integrative framework of Indonesian family law and provides practical recommendations for strengthening family development policies based on public welfare and family well-being at both local and national levels.